Social Media Content Calendar as a Tourism Marketing Strategy Design in Taro Tourism Village - Gede Karisma Wibawa; Denok Lestari; Francisca Titing Koerniawaty (Green Publisher Indonesia, 2025)
The purpose of this research is to design a tourism marketing strategy through Instagram and Facebook social media content suitable for Taro Tourism Village to increase brand awareness. The research uses qualitative methods with data collected from two main informants and one key informant through observation, interviews, and documentation. Data analysis includes data reduction, presentation, and drawing conclusions, while validity is tested using triangulation. The study finds that Taro Tourism Village lacks a clear and detailed social media marketing strategy, especially on Instagram and Facebook, to boost brand awareness effectively. The proposed tourism marketing strategy consists of eight stages: setting goals, target market mapping, content ideas and planning (including calendar content), content creation, content distribution, content strengthening, content marketing evaluation, and content development. This comprehensive content marketing approach is designed to fit the needs of Taro Tourism Village. The strategy’s implementation can be organized into a Social Media Content Calendar, serving as a practical tool for scheduling and managing content on Instagram and Facebook. This calendar aims to support the village's marketing efforts by improving consistency, clarity, and engagement with potential tourists, ultimately enhancing Taro Tourism Village’s brand awareness through social media channels.